A case study on the applicability of adaptive reuse theory Sarrat Presidencia Municipal Hall - Castro, Ma. Zenaida A.
The research determined the applicability of Adaptive Reuse Theory in Sarrat Presidencia municipal hall as the case study. The specific objectives of the study were to identify the elements of Adaptive Reuse Theory that were applied to the structure and to evaluate the effective use of the application of the theory to Sarrat Presidencia municipal hall. The data from the interview were gathered from eight (8) people. Purposive sample of respondents to get data on the Sarrat Presidencia municipal hall are based on the following criteria: they are employed in Sarrat municipal hall as local line employees and the respondents' ages ranged from twenty-one (21) to sixty (60) years old. All respondents are residents of the municipality of Sarrat, Ilocos Norte. They were chosen because they specifically experienced the new function and have the knowledge on what the structure used to be. Preliminary interviews to acquire the history and the current state of the structure were conducted. Ocular observation, photographic documentation and interviews were then employed in gathering data for the study. The data collected included the tabulation of interview made and a frequency count of the answers from the respondents. Summary of responses were converted into tables and pie charts. A detailed description for photo documentation and ocular observation was used to verify the results of the interview made. The data was analyzed using quantitative and qualitative approach and summarized into narrative form in relation to the identified elements of Adaptive Reuse Theory which are to keep the original core intact and its authentic architectural form retains. (Villalon 145) Results of the data collections include the following: repartitioned interior that accommodated the new function of the structure and the heritage design, in essence, was preserved but not its authentic architectural form which is one of the two requirements of the theory. The requirements of the Adaptive Reuse Theory were not implemented to its best because there were limitations like the non-availability of materials which resulted to not keeping the original core intact. The applicability of Adaptive Reuse Theory to Sarrat Presidencia was determined through the investigation of the requirements of the theory that were applied in the structure. The requirements of the theory were identified in the study. Two requirements of Adaptive Reuse Theory include, keeping the original core and retention of its authentic architectural form. These requirements were found to be nearly present in the structure but unfortunately the theory is applicable up to an extent because it has its limitations. The application of Adaptive Reuse Theory was effective in a way that the interior undergone repartitioning to accommodate its new function. The theory, according to Augusto F. Villalon, allows repartitioning of interior to accommodate the structure's new use. The researcher recommends that the new use of the structure be given importance especially in terms of its layout because this was found to be problematic.